The effect of CAPN1 and CAST gene variations on meat quality traits in Finnish Aberdeen Angus and Nordic Red Cattle populations - Iso-Touru, Terhi; Pesonen, Maiju; Fischer, Daniel; Huuskonen, Arto; Sironen, Anu (Agricultural and Food Science, 2018)
High meat quality and specifically meat tenderness are desired traits by the consumers, however the environmental impact of meat production is becoming a relevant factor in the industry. Therefore, breeding of dual purpose cattle breeds may answer the high demand of meat production in the future. In this study we identified statistical differences between genotypes of CAST and CAPN1 gene variants with meat quality traits in a dairy breed (Nordic Red Cattle) and compared the results with beef breed (Aberdeen Angus). Our results show that the favorable alleles have not been selected in the studied dairy breed and thus could be used as a tool for improvement of meat quality. The genes were associated with specific meat quality traits (i.e. sensory juiciness, marbling score and meat color) also in the dairy breed. This supports the utility of known meat quality associated genetic variants to improve meat quality in dairy breeds.